Evaluasi Penggunaan Antibiotik pada Pasien Pediatri ISPA dengan Metode Gyssens - Eva Najmah Novita; Ressi Susanti; Nurmainah Nurmainah (State University of Gorontalo, 2022)
Acute Respiratory Infection (ARI) is an upper or lower respiratory tract infection caused by a virus or bacteria. The high prevalence of ARI in Indonesian children can increase the risk of irrational use of antibiotics. This study aims to describe the types of antibiotics that are often used and analyze the rationality of antibiotics usage in pediatric ARI inpatient in Sultan Syarif Mohamad Alkadrie Public Hospital using the Gyssens method. This study is an observational study with a cross-sectional design. Data were collected retrospectively with consecutive sampling method. Data were analyzed using the Gyssens method based on therapeutic guidelines by IDAI, the Indonesian Ministry of Health, and WHO. The result showed that from 98 patients, the types of antibiotics were obtained as follows: third generation of cephalosporin group (66.16%), the penicillin group (19.23%), and the macrolide group (14.61%). Based on the results of the evaluation of antibiotics using the Gyssens method, the percentage of antibiotics usage that are in category 0 is 11,24%, category I (15,73%), category IIa (17,98%), category IIb (24,16%), category IIIa (0,56%), category IVa (15,73%), category IVc (1,69%), and category V (12,92%). It can be concluded that there is still irrational use of antibiotics in pediatric ARI inpatient in Sultan Syarif Mohamad Alkadrie Public Hospital in 2019-2020.